Campaign strategy notes
These handwritten campaign strategy notes outline key talking points contrasting Jane Tolmach with her opponent, Chuck Imbrecht. The notes emphasize attacking "hidden money" and alleged outside corporate funding in the Republican campaign, portraying Imbrecht as an outsider tied to the Nixon administration and backed by special interests. They propose highlighting local control, property tax relief, a four-year state college for Ventura County, effective representation, law and order, and Governor Brown's endorsement as positive themes. The document also includes side-by-side biographical comparisons, presenting Tolmach's long record of local public service against Imbrecht's recent return from Washington, D.C., to run for office. Overall, the notes reflect a planned strategy to frame the race as a choice between experienced local leadership and an outside-backed, inexperienced challenger.